Działalność Urzędu Patentowego w zakresie ochrony znaków towarowych na podstawie rozporządzenia o ochronie wynalazków, wzorów i znaków towarowych z 1928 roku — zarys problematyki - Dolata, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The aim of the paper is to discuss the work of the Patent Office with regard to the protection of trademarks under the 1928 Regulation on the Protection of Inventions, Designs and Trademarks. Given the long period it remained in force, the Regulation is the most reliable basis for investigating the matter. What remains outside the scope of the paper is a detailed discussion of the theoretical constructs used by the legislator to protect trademarks. Although these questions are obviously connected with the subject matter in question, they constitute a separate research problem.
Keywords: własność przemysłowa; znaki towarowe; II Rzeczpospolita; Urząd Patentowy